La Croix-Rouge double l'engagement qu'elle a pris en faveur des réfugiés Hongrois: Vent mille réfugiés vont recevoir l'aide de la Croix-Rouge en Autriche . Red Cross Doubles Commitments for Hungarian Refugee Aid: 20,000 Refugees in Austria Now to Receive Red Cross Care - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): League of Red Cross Societies